EAN consensus statement for management of patients with neurological diseases during the COVID‐19 pandemic. (15th October 2020) - von Oertzen, T. J.; Macerollo, A.; Leone, M. A.; Beghi, E.; Crean, M.; Oztuk, S.; Bassetti, C.; Twardzik, A.; Bereczki, D.; Di Liberto, G.; Helbok, R.; Oreja‐ Guevara, C.; et al.
Abstract : Background and purpose: The recent SARS‐CoV‐2 pandemic has posed multiple challenges to the practice of clinical neurology including recognition of emerging neurological complications and management of coexistent neurological diseases. In a fast‐evolving pandemic, evidence‐based studies are lacking in many areas. This paper presents European Academy of Neurology (EAN) expert consensus statements to guide neurologists caring for patients with COVID‐19. Methods: A refined Delphi methodology was applied. In round 1, statements were provided by EAN scientific panels (SPs). In round 2, these statements were circulated to SP members not involved in writing them, asking for agreement/disagreement. Items with agreement >70% were retained for round 3, in which SP co‐chairs rated importance on a five‐point Likert scale. Results were graded by importance and reported as consensus statements. Results: In round one, 70 statements were provided by 23 SPs. In round two, 259/1061 SP member responses were received. Fifty‐nine statements obtained >70% agreement and were retained. In round three, responses were received from 55 co‐chairs of 29 SPs. Whilst general recommendations related to prevention of COVID‐19 transmission had high levels of agreement and importance, opinion was more varied concerning statements related to therapy. Conclusion: This is the first structured consensus statement on good clinical practice in patients with neurological disease during the COVID‐19 pandemic that provides immediate guidance for neurologists. In this fast‐evolving pandemic, a rapid response using refined Delphi methodology is possible, but guidance may be subject to change as further evidence emerges.